Ethnic Group and Religion Along with Other Factors Affect The Spiritual Needs of The Elderly with Chronic Diseases in Indonesia - Arief Andriyanto; Ima Rahmawati; Emyk Windartik; Ana Zakiyah; Enny Virda Yuniarti (JURNAL INFO KESEHATAN, 2025)
Spirituality helps the elderly adapt to changes in themselves. The process of healing chronic diseases in the elderly requires good spirituality. However, in reality, many elderly people still have low spirituality. This study considers the factors of spiritual needs of elderly people with chronic illnesses in Indonesia. Descriptive correlation research design with a cross-sectional approach. The sample was 210 elderly people taken by purposive sampling. The independent variables studied include age, gender, religion, ethnic group, education, work, history of illness, ADL, and cognitive function. The dependent variable is spiritual needs. The research instrument in the form of the Spiritual Needs Questionnaire (SpNQ). A linear regression test to simultaneously correlate several dependent variables with independent variables by following several modeling assumptions. There is a significant relationship between religious factors (0.01), ethnicity (0.003), cognitive function (0.04), and the spiritual needs of elderly people with chronic diseases (<0.05). The equation obtained from modeling can predict the value of the spirituality needs of elderly people with chronic illnesses. Respondents who have sufficient spiritual needs because they are good at connecting with other people, nature/the environment, and God.